Efficacy and safety of delafloxacin, ceftaroline, ceftobiprole, and tigecycline for the empiric treatment of acute bacterial skin and skin structure infections: A network meta-analysis of randomized controlled trials - Abdullah A. Alhifany; Nisrin Bifari; Yasser Alatawi; Saad U. Malik; Thamer A. Almangour; Ali F. Altebainawi; Thamir M. Alshammari; Amal F. Alotaibi; Ahmad J. Mahrous; Fahad S. Alshehri; Ejaz Cheema (Elsevier, 2022)
Background: This review aimed to conduct an indirect comparison using a Bayesian network meta-analysis of randomized controlled trials (RCTs) to compare the efficacy and safety of delafloxacin versus other single antibiotic regimens for the empiric treatment of Acute Bacterial Skin and Skin Structure Infections. Method: A systematic search with no start date restrictions was conducted. The Cochrane Risk of Bias tool was used to assess the quality of included RCTs. Results: Of the 577 studies initially identified, nine RCTs were included in the review. The network meta-analysis showed that ceftaroline, ceftobiprole, delafloxacin and tigecycline had similar efficacy in the indirect comparisons [Ceftaroline Odds Ratio (OR) = 1.2, 95% Crl = 0.46-3.6), ceftobiprole (OR = 1.3, 95% Crl = 0.34-3.0) and tigecycline (OR = 0.96, 95% Crl = 0.30-2.9)]. However, the ranking plot for the intention to treat (ITT) population showed that delafloxacin had a probability of 80.8% to be ranked first followed by ceftobiprole (13.1%). The analysis of the overall adverse events showed that ceftaroline (OR = 0.88, 95% Crl = 0.65-1.2), ceftobiprole (OR = 1.1, 95% Crl = 0.69-2.0), delafloxacin (OR = 0.88, 95% Crl = 0.57-1.3) and tigecycline (OR = 1.4, 95% Crl = 0.88-2.2) had similar safety profiles. Conclusion: Delafloxacin did not show any statistically significant differences when compared to ceftaroline, ceftobiprole, and tigecycline in terms of efficacy and safety. However, the surface under the cumulative ranking curve (SUCRA) probability ranked delafloxacin as the first option for the ITT population.